2016
DOI: 10.1128/mcb.00773-15
|View full text |Cite|
|
Sign up to set email alerts
|

Utp14 Recruits and Activates the RNA Helicase Dhr1 To Undock U3 snoRNA from the Preribosome

Abstract: bIn eukaryotic ribosome biogenesis, U3 snoRNA base pairs with the pre-rRNA to promote its processing. However, U3 must be removed to allow folding of the central pseudoknot, a key feature of the small subunit. Previously, we showed that the DEAH/ RHA RNA helicase Dhr1 dislodges U3 from the pre-rRNA. DHR1 can be linked to UTP14, encoding an essential protein of the preribosome, through genetic interactions with the rRNA methyltransferase Bud23. Here, we report that Utp14 regulates Dhr1. Mutations within a discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 40 publications
7
94
0
Order By: Relevance
“…Dismantling of the 90S preribosome is likely to depend on the RNA helicase Dhr1, since pre-40S intermediates trapped by catalytically inactive Dhr1 still contain the U3 snoRNP [67]. Moreover, Dhr1, stimulated by its recruiting cofactor Utp14, can unwind U3 rRNA duplexes in vitro [67,68]…”
Section: Dismantling Of the 90s Preribosome Releases An Early Pre-40smentioning
confidence: 99%
“…Dismantling of the 90S preribosome is likely to depend on the RNA helicase Dhr1, since pre-40S intermediates trapped by catalytically inactive Dhr1 still contain the U3 snoRNP [67]. Moreover, Dhr1, stimulated by its recruiting cofactor Utp14, can unwind U3 rRNA duplexes in vitro [67,68]…”
Section: Dismantling Of the 90s Preribosome Releases An Early Pre-40smentioning
confidence: 99%
“…UTP14 is a subunit of the U3 containing small subunit (SSU) processome complex, and interacts with the preribosome. As a member of the UTP14 family, UTP14a is also involved in ribosome biogenesis and 18S rRNA synthesis . Some studies found that the expression of UTP14a is upregulated in human hepatocellular carcinoma and colorectal carcinoma, and it may be associated with poor prognosis …”
Section: Discussionmentioning
confidence: 99%
“…As a member of the UTP14 family, UTP14a is also involved in ribosome biogenesis and 18S rRNA synthesis. 7,8 Some studies found that the expression of UTP14a is upregulated in human hepatocellular carcinoma and colorectal carcinoma, and it may be associated with poor prognosis. 12,13 In this study, UTP14a was positively expressed in 88.1% of the ESCC samples, and 30% of CDM samples exhibited positive expression; Western blot analysis further confirmed that the protein levels of UTP14a were significantly higher in ESCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations